Does Ventriloquism Break the Place and Manner of Articulation Principles? Case Study of Jeff Dunham - Rizqy, Agis Zalfa Verenia Nur; Zulferdi, Lazuar Azmi (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study investigates the adaptability of place and manner of articulation principles in ventriloquism. It analyzes Jeff Dunham’s instructional techniques in his 11-part series How to Be a Ventriloquist, comparing them with traditional Indonesian methods documented in Marijoen’s Pintar Bermain Sulap Suara. The research identifies sound substitutions that maintain vocal distinctiveness without visible lip movement. The findings show that ventriloquism does not violate phonetic principles but demonstrates the flexibility of the human speech system through adaptive strategies. For example, bilabial stops /b/ and /p/ are replaced with alveolar stops /d/ and /t/, and labiodental fricatives /f/ and /v/ are substituted with interdental fricatives /θ/ and /ð/. A comparison of American and Indonesian techniques reveals cross-cultural convergence in these substitution strategies, supporting universal principles of speech adaptation under constraints. These findings contribute to articulatory phonetics by suggesting that acoustic-perceptual targets drive speech production, even when articulation is restricted. The study also has practical implications for speech therapy and second language acquisition, offering strategies for individuals with speech impairments or those learning challenging sounds. Further research is needed to quantify the effectiveness of these substitutions and explore optimal training methods for ventriloquism.